Differences among clinical isolates of Pseudomonas aeruginosa in their capability of forming biofilms and their susceptibility to antibiotics (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Wahyudi D, Aman AT, Handayani NSN, Soetarto ES. 2019. Differences among clinical isolates of Pseudomonas aeruginosa in their capability of forming biofilms and their susceptibility to antibiotics. Biodiversitas 20: 1450-1456. Pseudomonas aeruginosa is an important nosocomial pathogen capable of causing both acute and chronic infections. The individuals of this bacterium have differences in their capability of forming biofilms.  Biofilm is a collection of bacterial cells attached to the tissue, coated by polysaccharides and extracellular matrix, enabling bacteria to become resistant to antibiotics, so infection is difficult to treat.  The aim of this study was to know the differences among clinical isolates of Pseudomonas aeruginosa in their capability of forming biofilms, and their susceptibility to some antibiotics. The bacteria were isolated from various patient samples at Dr. Moewardi Hospital Surakarta, Indonesia, from August to December 2017. The isolates were purified using single cell colony technique.  The bacterial identification and tests of susceptibility to many antibiotic were conducted using automatic equipment (vitex® 2). Test method of biofilm formation was done using the Tissue Culture Plate. The readings of results were monitored spectrophotometrically at a wavelength of 570 nm and repeated 8 times. DNA isolation was done using Qiagen DNeasy Blood and Tissue Kit, and gene identification (pelD and pslA) was done using PCR (Polymerase Chain Reaction) and visualization through electrophoresis.  The results showed that of the 64 isolates of P. aeruginosa from blood, sputum, urine, ear middle, urine catheter, pleural fluid, pus, stool, aspirate, and cerebrospinal, 22% were low in forming biofilm, 50% moderate, and 28% high. Isolates of P. aeruginosa were resistant to ampicillin, cefazolin, tigecycline, nirofurantoin, and cotrimoxazole, but sensitive to piperacillin, ceftazidime, cefepime, aztreonam, meropenem, amikacin, gentamicin, and ciprofloxacin. The genes of pelD and pslA were present in all P. aeruginosa isolates (low, moderate, dan high).   In conclusion, P. aeruginosa clinical isolates had different capability of forming biofilms and susceptibility to antibiotics. Isolates having high ability to form biofilm were relatively more resistant to many antibiotics. They were most sensitive to amikacin and resistant to ampicillin.  There was no difference in the presence of mop pelD and pslA among all isolates.
Keywords: Pseudomonas aeruginosa, biofilm, susceptibility antibiotic